Ultrastrong Terahertz Emission from InN Nanopyramids on Single Crystal ZnO Substrates. Issue 11 (9th May 2017) - Liu, Huiqiang; Chen, Zuxin; Chu, Sheng; Chen, Xuechen; Liu, Min; Peng, Nan; Chu, Guang; Huang, Feng; Peng, Rufang
Abstract : The creation of high efficiency and room temperature terahertz (THz) emitters has long been expected in both scientific and industrial communities. Despite the recent progress in THz source such as quantum cascade lasers, high efficiency THz emitters capable of operating at room temperature are still elusive. Indium nitride (InN), a narrow bandgap semiconductor, has emerged as a promising THz emitter due to its unique electronic properties. However, the efficiency of InN THz emitters reported up to now is still far from theoretically predicted because of inadequately engineered electrical conduction and radiative coupling. In this study, the authors report a novel, high performance THz emitting structure consisting of nanoengineered InN micro/nanopyramid arrays on a single crystal zinc oxide (ZnO) substrate. With improved electronic conduction from Zn diffusion induced doping and enhanced radiation coupling benefiting from uniquely structured geometry, the InN nanopyramids yielded THz emission intensity is close to an order of magnitude stronger than that of p‐type indium arsenide (InAs). These findings prove that InN is a promising THz material and of wide importance in material science, optical engineering sectors, etc. Abstract : A novel, high performance temperature terahertz (THz)‐emitting structure is reported consisting of nanoengineered Indium nitride (InN) micro/nanopyramid arrays on a single crystal zinc oxide substrate. With improved electronic conduction as a result of Zn‐diffusion‐induced doping and enhanced radiation coupling due to uniquely structured geometry, the InN nanopyramids‐yielded THz emission intensity (the THz emission peak is around 0.5 THz) is close to an order of magnitude stronger than that of p‐type InAs.